2017
DOI: 10.1186/s13756-017-0252-6
|View full text |Cite
|
Sign up to set email alerts
|

Epidemic characterization and molecular genotyping of Shigella flexneri isolated from calves with diarrhea in Northwest China

Abstract: BackgroundThe widespread presence of antibiotics resistance genes in pathogenic bacteria can cause enormous problems. Food animals are one of the main reservoirs of intestinal pathogens that pose a potential risk to human. Analyzing the epidemiological characteristics and resistance patterns of Shigella flexneri in calves is necessary for animal and human health.Methods and resultsA total of 54 Shigella flexneri isolates, including six serotypes (1a, 2a, 2b, 4a, 6 and Xv), were collected from 837 fecal samples… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
24
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 27 publications
(25 citation statements)
references
References 44 publications
(45 reference statements)
1
24
0
Order By: Relevance
“…qnr genes, which are often incorporated into integrons, may allow for dissemination among Shigella and possibly other members of the Enterobacteriaceae family, and then quinolone-resistance isolates may spread across geographic regions and even across countries with population mobility 65,67. The aac(6′)-Ib-cr gene encodes an acetyltransferase associated with reduced quinolone activity, and is identified in many members of the Enterobacteriaceae family 68. PMQRs have been identified widely among human and animal isolates, and have become a pressing issue worldwide.…”
Section: Drug-resistance Mechanisms In Shigella Sppmentioning
confidence: 99%
“…qnr genes, which are often incorporated into integrons, may allow for dissemination among Shigella and possibly other members of the Enterobacteriaceae family, and then quinolone-resistance isolates may spread across geographic regions and even across countries with population mobility 65,67. The aac(6′)-Ib-cr gene encodes an acetyltransferase associated with reduced quinolone activity, and is identified in many members of the Enterobacteriaceae family 68. PMQRs have been identified widely among human and animal isolates, and have become a pressing issue worldwide.…”
Section: Drug-resistance Mechanisms In Shigella Sppmentioning
confidence: 99%
“…It has been reported that aac(6')-Ib-cr signi cantly increases the frequency of selection of chromosomal mutants to reduce cipro oxacin activity by N-acetylation at the amino nitrogen on its piperazinyl substituent [36]. The aac(6')-Ib-cr-positive Shigella was rst isolated in 1998 [37]; however, the most striking nding of our previous and present study was the aac(6′)-Ib-cr allele wide penetration in all quinolone-resistant isolates [38,39]. The qnr family could protect DNA gyrase against quinolones and confer low-level resistance to nalidixic acid and reduced susceptibility to uoroquinolone, especially to cipro oxacin [40].…”
Section: Discussionmentioning
confidence: 59%
“…40 The aac(6')-Ib-cr-positive Shigella was rst isolated in 1998; 41 however, the most striking nding of our previous and present study was the aac(6′)-Ib-cr allele wide penetration in all quinolone-resistant isolates. 42,43 The qnr family could protect DNA gyrase against quinolones and confer low-level resistance to nalidixic acid and reduced susceptibility to uoroquinolone, especially to cipro oxacin. 44 The qnr gene has occurred worldwide and contains a variety of subtypes, but it was not a common epidemic genotype according to our study.…”
Section: Discussionmentioning
confidence: 99%